Revolutionizing Welding Ergonomics to Mitigate Musculoskeletal Risks: Merevolusi Ergonomi Pengelasan untuk Mengurangi Risiko Muskuloskeletal - Isma Putra, Boy; Khatamy, Mohammad Reza (Indonesian Journal of Innovation Studies, 2024)
This study examines ergonomic challenges faced by welders at CV. Frontec Agritama Engineering, focusing on catwalk welding. Using Rapid Entire Body Assessment (REBA) and Quick Exposure Check (QEC), ergonomic risks were evaluated. Results showed high-risk levels, urging immediate interventions. Proposed solutions include ergonomic workstations to reduce musculoskeletal injuries. This research contributes to workplace safety and productivity in manufacturing. Highlight: REBA and QEC methods assess ergonomic risks comprehensively. Welding activities pose significant musculoskeletal risks. Proposed ergonomic workstations enhance safety and productivity. Keywoard: Ergonomics, Welding, Manufacturing, Musculoskeletal Risks, Workplace Safety